Cancer Cell Signaling 2014
DOI: 10.1201/b17138-9
|View full text |Cite
|
Sign up to set email alerts
|

Wnt3a Expression is Associated with MMP-9 Expression in Primary Tumor and Metastatic Site in Recurrent or Stage IV Colorectal Cancer

Abstract: Infantile hemangioma (IH), which is the most common tumor in infants, is a benign vascular neoplasm resulting from the abnormal proliferation of endothelial cells and pericytes. For nearly a century, researchers have noted that IH exhibits diverse and often dramatic clinical behaviors. On the one hand, most lesions pose no threat or potential for complication and resolve spontaneously without concern in most children with IH. On the other hand, approximately 10% of IHs are destructive, disfiguring and even vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 66 publications
2
21
0
Order By: Relevance
“…Interestingly, we did observe the induction of p27 kip1 following Notch stimulation of Hem-pericytes, further supporting the idea of cell-specific activation of Notch effector molecules [29].…”
Section: Cip1supporting
confidence: 66%
See 1 more Smart Citation
“…Interestingly, we did observe the induction of p27 kip1 following Notch stimulation of Hem-pericytes, further supporting the idea of cell-specific activation of Notch effector molecules [29].…”
Section: Cip1supporting
confidence: 66%
“…We proceeded based on our previous supposition that the Notch pathway might also contribute to establishing two distinct subpopulations at different steps of angiogenesis in IHs, such as ECs versus pericytes [29,37,38]. We demonstrated that the Jagged1 level was increased in involuting IH tissues [15].…”
Section: Cip1mentioning
confidence: 99%
“…In the present study, we found that knockdown of IGF2R could significantly downregulate the expression of PCNA, Ki-67, Bcl-2, Cyclin D1 and E and upregulated the expression of Bax in HA cells and xenograft HA samples, suggesting that IGF2R may promote the development and progression of human HA via upregulation of PCNA, Ki-67, Bcl-2, Cyclin D1 and E expression and downregulation of Bax expression. More importantly, PI3K/AKT has been found to play a role in the development of HAs (20,21). Activation of the PI3K/AKT pathway promotes tumor growth and invasion through upregulation of the PCNA and Ki-67 expression (33), blocks cell apoptosis through decrease of the Bax/Bcl-2 ratio (34), and prompts cell cycle progression through upregulation of Cyclin D/E expression (35).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that the PI3K/AKT pathway is involved in regulating HA formation (20,21). Whether Lv-siIGF2R affects PI3K/AKT signaling transduction of PI3K/AKT needed to be explored.…”
Section: Effect Of Lv-siigf2r On Signaling Transduction Of Pi3k/aktmentioning
confidence: 99%
“…We still do not understand the complex biology of its rapid proliferation and spontaneous regression. However, some light has been recently shed on signaling pathways involved in these processes such as VEGF/VEGFR, Notch, Tie2/Angiopoetin, HIF␣, PI3 K/Akt/mTOR, PDGF-B/PDGFR-beta and B-adrenergic [1][2][3]. Some of these tumors, especially in proliferating phase interfere physiological functions or * Corresponding author at: Sporna Str 36/50, 91-738 Lodz, Poland.…”
Section: Introductionmentioning
confidence: 97%